1996
DOI: 10.1111/j.1752-7325.1996.tb02389.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dental Sealants by Ohio Dentists

Abstract: The grate majority of Ohio dentists report using sealants. The percent of reported sealant users increased between 1989 and 1992. Ohio dentists are not consistent with regard to the percent of their child patients for whom they apply sealants or their willingness to seal incipient caries. Dentists continue to identify lack of insurance coverage for sealant application as a major barrier to patients receiving the service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0
4

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 26 publications
(23 reference statements)
3
14
0
4
Order By: Relevance
“…This finding is in agreement with the north American studies which show that high percentage of dentists employ fissure sealants wherever indicated. [12,20] Regarding use of Fluoride, our findings match results of an American study6 but fluoride varnish is underutilized by respondents of this study as well as another study done to assess CAMBRA-based programs in North American dental Schools. [22] May be unlike fluoride gel, role of varnish has not been appropriately emphasized during undergraduate classes.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is in agreement with the north American studies which show that high percentage of dentists employ fissure sealants wherever indicated. [12,20] Regarding use of Fluoride, our findings match results of an American study6 but fluoride varnish is underutilized by respondents of this study as well as another study done to assess CAMBRA-based programs in North American dental Schools. [22] May be unlike fluoride gel, role of varnish has not been appropriately emphasized during undergraduate classes.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, in USA after two decades, the students who received the preventive -based training when became clinicians Section: Dentistry started practicing it and the idea to treat caries by surgical intervention is gradually being replaced by preventive approaches. [17][18][19][20][21][22] Like many other countries, Pakistan seems to be a country where the dentists don't follow preventive -based protocols in their clinical practices. According to a study done very recently, dentists from Pakistan working in Saudi Arabia were found to place intracoronal restorations as a primary solution to treat caries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the survey also showed that the decision not to adopt a technology, such as sealants for adults or fluoride varnishes, was related to cost or the lack of coverage by insurance and a perceived lack of caries risk by the adult patients and thus reduced benefit to the procedure. Other survey‐based studies have reached similar conclusions (4). In a repeat survey by Fiset and Grembowski (10) conducted in 1997 after the Washington State Dental Service began reimbursing for fluoride varnish, use had increased significantly, but only to 44% (from 32%), suggesting that reimbursement alone was not the most important factor.…”
supporting
confidence: 74%
“…Many studies have reported on the use of caries preventive agents in children (6,11,15-20) whereas others have reported on their effectiveness in achieving improved oral outcomes (9,21-24). Fewer studies have focused on the use of prevention in adults (25-28).…”
Section: Discussonmentioning
confidence: 99%